Atmospheric Turbidity of Solar Radiation over Langtang National Park - Shrestha, Prakash M.; Karki, Indra B.; Chapagain, Narayan P.; Poudyal, Khem N. (Journal of Nepal Physical Society, 2022)
The main aim of this project is to study atmospheric turbidity of solar radiation over Langtang National Park (28.2112° N, 85.5663° E and altitude 3862 m a.s.l.). The daily aerosol optical depth (AOD) data are derived from Aerosol robotic network (AERONET) for a period of one year 2018. Annual mean of Angstrom exponential (α), Angstrom turbidity coefficient (β) and curvature of AOD (a2) are found 1.04 ± 0.29, 0.03± 0.02 and 4.1 ± 0.9 respectively. The average value of and Linke turbidity (LT) is 2.5 ± 0.6. Result of this research work is beneficial for the further identification, impact and analysis of atmospheric turbidity factors at different places.